Exploring the influence of sensory marketing on brand perception - Zoran Krupka (Naše gospodarstvo / Our Economy, 2023)
The main purpose of this paper is to investigate how the number, perceived intensity, and frequency of sensory involvement in the consumer-brand relationship, impact brand perception. The research was conducted on a sample of 189 respondents from the Republic of Croatia. To test the hypotheses factor and regression analyses were used. The main findings of this research are: a) involvement of multiple senses in the consumer-brand relationship has a positive effect on brand perception; b) the greater the frequency of involving multiple senses in the consumer-brand relationship, the more positive effect it has on brand perception; and c) the higher intensity of sensory involvement in the consumer-brand relationship does not have a significant effect on brand perception. This research contributes to marketing and brand management literature by investigating importance of sensory marketing, more specifically number, perceived intensity, and frequency of sensory involvement on brand perception.
Keywords: M30; M31; 330; Brand; Sensory marketing; Brand perception